Pelatihan Microgreen dan Hidroponik di SPPSA Kota Bandung Guna Meningkatkan Kreativitas dan Produktivitas Anak - Karlisa Priandana; Sarah Arisanti; Karina Eku Dwinanda Gunawan; Nazala Hafidhullah; M Alwan Farhandany (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
This article discusses one of the activities in the 2020 IPB University’s KKN-T Program, which is a form of IPB's concern for the community in handling Covid-19 and post-Covid-19. This activity focuses on handling the impact of Covid-19 and making plans for a post-Covid-19 recovery program with partners in the Child Social Protection Service Unit (CSPSU) in Bandung City. Activities carried out included training in microgreen planting, training in hydroponic cultivation and making anti-Covid-19 propaganda posters. The training is conducted both theoretically and direct practice in the field. The purpose of this activity is to increase student and children's awareness of the Covid-19 pandemic, help increase the effectiveness of children's learning processes during the Covid-19 pandemic, increase children's creativity and productivity, and increase children's awareness of the importance of maintaining the health of themselves and others. In addition, this activity also aims to train children to have basic abilities to live independently, with activities that have minimal physical interaction with the outside environment, in order to comply with health protocols during the Covid-19 pandemic. Keywords: children, bandung, covid-19, kknt ipb, post covid-19, handling.